عناصر المزيج التسويقي لخدمات التدقيق: دراسة تحليلية لتفضيلات الزبائن والمهنيين (Journal of Accounting and Financial Studies ( JAFS ), 2011)
The research seeks to determine the nature of audit services, their characteristics and the basic concepts of services marketing audit and definition of the rules and basic dimensions of the marketing audit services through the knowledge of the elements of the marketing mix and test the preferences of customers and auditors of the factors affecting the marketing audit services by selecting a sample of the owners of some of the projects and companies and a sample of auditors has been use the resolution to achieve the objectives of the research where a good question to the owners about the most important factors in your choice of the Audit Office and asked the organization to answer according to the standard trio (very important, a few important, not important) have been identified (12) factor. The questionnaire included with which the auditors of the factors that are more important to market their services and ensure the question (12) factor also research found a set of results, mainly the lack of many professionals to how to reach customers and how it defines its services to their lack of marketing skills for promoting effective services and some of them adopt negative views toward marketing holds that marketing activity is a professional and even immoral, and promotion services depends on the philosophy that good practice for the work are capable of growth and quality reputation of the profession that will benefit him more than acting.